Councils of churches and the ecumenical vision - Kessler, Diane; Kinnamon, Michael (Geneva (SZ) : WCC, World Council of Churches, 2000)
El futuro del movimiento ecuménico.
Keywords: RELIGION; TEOLOGIA; ECUMENISMO -- HISTORIA; ECUMENISMO -- S. XXI; ESPERITUALIDAD -- ECUMENISMO; LIDERAZCO -- ECUMENICO